Gender Equality in Batak Toba Society in the Lights of the Theological Thoughts of Ivone Gebara - Rina Elysa Sinurat; Moses Putra Gautama; Andreas Ama Kelen; JB. Heru Prakosa (Fakultas Teologi, Universitas Sanata Dharma, 2024)
In the shadow of strong traditional customs, Batak Toba women are subjected to the authority of men, be it husbands or male relatives, and are confined to the role of Parhobas (servants) for every family event. Ivone Gebara's thoughts would provide inspiration to address the challenges of gender inequality through empowering women and inclusive human values in open dialogue, aiming for personal and social transformations that are inclusive, just, and sustainable, following the social-cultural context of Batak Toba in Indonesia. The focus of Ivone Gebara's theological thought aligns with the principles of Liberation Theology, emphasizing the importance of efforts to connect the Christian faith with the lives of communities affected by social and economic injustice, along with solidarity with the poor and oppressed. This research used a literature review method by examining recent articles on Ivone Gebara's thoughts. She critically observes the patriarchal structures in society and the Church, advocating for the need for critical reflection in inclusive and egalitarian interpretations of women's experiences to promote gender equality. Gebara's thoughts serve as a foundation to enrich public narratives and support education and feminist awareness for social change within the Batak Toba community. Contextualizing Gebara's ideas in Indonesia, particularly in the Batak Toba culture, can support movements and awareness regarding religious norms and encourage open discussions about women's roles in diverse societies.